«Verso il sesso unico»: rituali metamorfici e travasamenti erotici nella prospettiva abumanista di Beniamino Joppolo (Mantichora. Italian Journal of Performance Studies, 2020)
Ambiguous sexual identity of androgynous paradigm, with its occult and esoteric meanings in Symbolism, becomes like a fluid performance of exchange between gender’s codes in Beniamino Joppolo’s intertext. In this direction, an important intermediary role is played by Futurism’s universe of sense and representation. The Feminine and Masculine appear as unstable and hybrid signs, through a perturbing strategy of displacement and disguise, according to the Joppolo and Audiberti’s abhumanism theory: fusion of the opposites, that are reconciled in a panic and fully developed monad identity. The inversion of traditional gender’s roles, with the body and its masks (fetish-clothes) in erotic metamorphosis – changing also language, behavioral positions, self-perception –, happens on several levels; and the relationship between the sexes turns from physical encounter into metaphysical consistency.